Cybersecurity in cloud computing environments - Bohdan Ilchenko; Olena Hurska; Гурська Олена (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. In recent years, cloud computing has become one of the most rapidly developing areas of information technology. Owing to its scalability, flexibility, and cost efficiency, cloud computing has become integral to business operations, education, healthcare, and scientific research. However, as more people use cloud technology, the number and complexity of cyber threats also rise. This situation highlights the urgent need for effective cybersecurity measures in cloud computing environments. The relevance of this research lies in the growing dependency on cloud-based systems and the consequent need to secure them against evolving attacks. The novelty of the study is determined by the integration of recent technological advancements, such as artificial intelligence, blockchain, and quantum cryptography, into the field of cybersecurity. The objective of this thesis is to analyze the main risks associated with cloud computing and to examine the most effective modern and emerging methods for ensuring cybersecurity in these environments. The transition to cloud-based infrastructure introduces new vulnerabilities and attack surfaces for cybercriminals. Unlike traditional IT systems, where organizations maintain full control over access and security policies, cloud resources are typically shared among multiple users and accessible over the Internet. This makes it easier for unauthorized people to get in and cause trouble.
Teljes kiadvány: https://kme.org.ua/uk/publications/rol-bezpeki-v-transkordonnomu-ta-mizhnarodnomu-spivrobitnictvi/
Keywords: Application Programming Interfaces (API); Distributed Denial of Service (DDoS); cloud computing; cybersecurity